Konsep Penataan Ruang Terbuka Hijau Publik Di Kota Kecamatan Mengwi, Kabupaten Badung, Provinsi Bali - DHARMADIATMIKA, I MADE AGUS (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017, 2017)
The purpose of this paper is to determine a plan of action structuring public green open space in the City of Mengwi, Knowing efforts to increase the quantity of green space in the City of Mengwi, and know the concept of development and structuring of public green open space in the City of Mengwi. This paper uses a qualitative approach with a phenomenological approach. The action plan structuring public green open space in the City of Mengwi action oriented with using this type of local parks, the action attribute applicative green city, square garden action, and action structuring neighborhood parks. Improving the quality of green space through enhancing functionality of existing green space, an increase in the proportion of green space utilization through neighborhood scale park like garden telajakan so that the amount of public open space can grow. The concept of the development of public green space in the City of Mengwi is based on the concept of implementing arrangement with green attributes, use local vegetation and observe the movement of the user system. Maximizing green space telajakan began by supplying bags garden is in the area of commercial and office.